Advances in data mining : applications and theoretical aspects : 15th Industrial Conference, ICDM 2015, Hamburg, Germany, July 11-24, 2015, Proceedings /: applications and theoretical aspects : 15th Industrial Conference, ICDM 2015, Hamburg, Germany, July 11-24, 2015, Proceedings. (2015) - Unknown
No abstract available